ANALISIS SWOT SEBAGAI LANDASAN MENENTUKAN STRATEGI PEMASARAN PT. SAMEKARINDO INDAH CABANG SANGATTA - Nelly, Nelly (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
The purpose of this research was to know the internal factors, the external factors and to determine company marketing strategy based on SWOT analysis where  were 4P marketing mix (product, price, promotion and place) as variable in this research. Analytical techniques were used  by using SWOT analysis to analyze the strengths, weaknesses, opportunities, and threats faced by companies therefore  to formulate appropriate marketing strategies.The results of this research was conducted at PT. Samekarindo Indah Sangatta which is internal branches have a good 3.25 stated value, external conditions have a good value of 3.07 otherwise. The position of the company is currently in the growth phase, this result was evidenced by the internal and external SWOT matrix which showed the state of the company was in cell 1. The Appropriate strategy applied PT. Samekarindo Indah Sangatta branch is using SO strategy (Strength Opportunities).